MOTIVATION OF FARMER GROUP MEMBERS IN THE USE OF HUMIC ACID IN SHALLOT CULTIVATION IN CILAWU DISTRICT, GARUT REGENCY - Musyarofah, Neni; Yoyon Haryanto; Fadila (Jurnal Penyuluhan Pertanian, 2023)
Soil fertility decrease on agricultural land due to the continuous use of chemical fertilizers and pesticide residues. Increasing farmer awareness of the use of other nutrient sources that are more eco-friendly. This research was conducted to determine the level of motivation; identify the motivation influencing factor; and develop strategies to increase farmers' motivation in using humic acid in shallot cultivation. This research was conducted from March to June 2022 in Cilawu District, Garut Regency. A descriptive method and multiple linear regression are used. Respondents were taken as many as 74 people who were determined by purposive sampling method, namely selected farmers who are members of farmer groups and cultivate shallot. The results show that the level of motivation was included in the medium category. A significant factor affected is the role of extension agents, the availability of facilities and infrastructure, and agricultural information. The strategy applied the extension to farmer’s approach to the most critical influent indicators, namely the availability of agriculture information